Which somatic symptoms are associated with an unfavorable course in Asian patients with major depressive disorder? - Novick, Diego; Montgomery, William; Aguado, Jaume; Kadziola, Zbigniew; Peng, Xiaomei; Brugnoli, Roberto; Haro, Josep Maria (Journal of affective disorders, 2013)
To investigate the impact of somatic symptoms on the severity and course of depression in Asian patients treated for an acute episode of major depressive disorder (MDD). Three-month prospective observational study of 917 patients with MDD in psychiatric care settings of which 909 had complete main baseline data. Depression severity was assessed using the physician-rated Clinical Global Impression of Severity (CGI-S) and 17-item Hamilton Depression Rating Scale (HAMD17), and somatic symptoms were assessed using the patient-rated 28-item Somatic Symptom Inventory (SSI). Cluster analysis using baseline SSI scores grouped patients into 3 clusters with no/few, moderate or severe somatic symptoms. Four factors of SSI (pain, autonomic symptoms, energy, and central nervous system) were defined and regression analyses identified which factors were associated with remission and response at 3 months follow-up. Baseline depression severity (HAMD17 and CGI-S scores) was associated with more severe somatic symptoms. Remission rates differed between clusters of patients: 68.4%, 54.7% and 29.3% for no/few, moderate and severe somatic symptoms, respectively (p<0.0001). Corresponding response rates were 81.8%, 72.1% and 55.2% (p<0.0001). Pain symptoms were the somatic symptoms most associated with these clinical outcomes at 3 months. Only patients diagnosed with MDD in psychiatric care were assessed. Somatic symptoms are frequent among Asian patients in psychiatric care for MDD and are associated with greater clinical severity and lower response and remission rates. Among somatic symptoms, pain symptoms have the greatest prognostic value and should be taken into account when treating patients with depression.